THE SHARIA ROLE OF THE MEDIA IN MODERN ISLAMIC STATES - Dr. Muhammad Riaz (International Journal of Contemporary Issues in Social Sciences, 2024)
This research article examines the role of mass media in modern Islamic states from a Shariah perspective. It argues that the current situation is ambiguous and lacks clarity, with authorities and rulers not definitively outlining the limits, responsibilities, and constraints that govern the mass media. Despite this ambiguity, mass media outlets generally operate with a degree of freedom, although this freedom is not absolute and can be weakened, limited, or even entirely restricted in the face of state oppression. The article begins by discussing the concept of Shariah and its relationship to the mass media. It then examines the specific responsibilities of mass media in an Islamic state, including the obligation to promote Islamic values, the prohibition of spreading false information, and the duty to provide accurate and objective reporting. The article concludes by arguing that the mass media can play a vital role in promoting a just and equitable society in accordance with Shariah principles. However, it also acknowledges the challenges that the mass media face in operating within the context of an Islamic state.